2021
DOI: 10.1016/j.ebiom.2021.103475
|View full text |Cite
|
Sign up to set email alerts
|

Early-life gut microbiota and its connection to metabolic health in children: Perspective on ecological drivers and need for quantitative approach

Abstract: The colonisation and development of the gut microbiota has been implicated in paediatric metabolic disorders via its powerful effect on host metabolic and immune homeostasis. Here we summarise the evidence from human studies on the early gut microbiota and paediatric overweight and obesity. Manipulation of the early gut microbiota may represent a promising target for countering the burgeoning metabolic disorders in the paediatric population, provided the assembly patterns of microbiota and their health consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 137 publications
(165 reference statements)
0
25
0
6
Order By: Relevance
“…Several studies have shown that the early-life microbiota plays a mediating role in host metabolic processes. Gut microbes are essential intermediaries in a wide range of mechanisms, including energy harvest, fat storage, regulation of lipid and glucose metabolism, induction of low-grade inflammation, gut barrier function, control of satiety through gut hormones, and interactions with host genetics [54,55]. To put it simply, the contribution of microbiota to the aforementioned mechanisms is based both on its metabolites, mainly (but not only) short-chain fatty acids (SCFAs), and on the activity of lipopolysaccharides (LPS) and bile acids [55].…”
Section: Microbiota and Host Metabolism Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the early-life microbiota plays a mediating role in host metabolic processes. Gut microbes are essential intermediaries in a wide range of mechanisms, including energy harvest, fat storage, regulation of lipid and glucose metabolism, induction of low-grade inflammation, gut barrier function, control of satiety through gut hormones, and interactions with host genetics [54,55]. To put it simply, the contribution of microbiota to the aforementioned mechanisms is based both on its metabolites, mainly (but not only) short-chain fatty acids (SCFAs), and on the activity of lipopolysaccharides (LPS) and bile acids [55].…”
Section: Microbiota and Host Metabolism Regulationmentioning
confidence: 99%
“…Therefore, it can be concluded that the excessive ponderal growth that characterizes obese children may be associated with an increased abundance of bacteria producing LPS. However, it is not entirely clear what role different LPS-producing bacteria play in the pathophysiology of excessive weight gain or early education of immunity in children [55].…”
Section: Microbiota and Lipopolysaccharidesmentioning
confidence: 99%
“…The effects of external factors, such as birth mode, antibiotic therapies, and diet, are relatively well studied. On the other hand, the mechanisms involved in the infant gut regulation (e.g., secretion of mucus glycans, immunoglobulin A, and bile acids) and in the microbial community dynamics (e.g., bacterial growth or replication rates, the interaction between the community members) remains poorly understood [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a simplified concept, the fetal development is characterized by the acquisition of immuno-tolerance towards maternal and self-antigens, whereas the neonatal period reflects the acquisition of immune-defense against potentially harmful environmental antigen. Immune development involves a complex cross talk of immune cells in various organs that is influenced by environmental antigen ( 1 3 ). During infancy and childhood, autoimmune diseases and chronic inflammation coincide with an exponential diversification of the adaptive immune system, causing potentially life-long consequences.…”
Section: Introductionmentioning
confidence: 99%